Total synthesis of (+)-isolaurepan - Tripathi, Divya; Kumar, Pradeep (Tetrahedron Letters, 2008)
A versatile and efficient method for the enantioselective synthesis of 2,7-cis-disubstituted oxepane 1c, (+)-isolaurepan, using oxidative resolution of a secondary alcohol and highly diastereoselective Et(3)SiH/TMSOTf-promoted reductive cyclization of a hydroxy ketone is described. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cis-selective cyclization; Cyclic ethers; Isolaurepan; Oxepanes; Oxidative resolution of secondary alcohols